Symbolism and Ritual Practice: The Role of Fruits in Buddhist Ceremonies at Maha Vihara Maitreya Medan, Indonesia - M. Yuda Prayoga; Jufri Naldo (Bulletin of Indonesian Islamic Studies, 2025)
The fruit offering ritual in Buddhist religious practices at the Maha Vihara Maitreya Cemara Asri in Medan represents symbolism rich in theological and ethical meaning. This study aims to examine in depth the symbolic meaning of fruit in Buddhist worship and uncover its connection to the concepts of abundance and purity in Buddhist teachings. Using a qualitative approach, participatory observation methods, in-depth interviews with religious leaders, and triangulation to ensure accuracy and validity, the information obtained in this study found that fruit is positioned not only as a material offering, but also as an expression of the congregation's inner spirit, embodying the values of dāna (generosity), belief in the law of karma, and hope for virtue. Fruits such as apples and oranges are chosen because they reflect freshness, propriety, and prosperity, while fruits such as durian are avoided because they are considered to reflect less inner refinement and a sacred atmosphere. Fruit symbolism in rituals also serves as a medium for internalizing the teachings of impermanence (anicca) and the consequences of actions (vipaka), reinforcing reminders of moral action, reflections on inner qualities, and ways to visualize spiritual values in everyday life. This research enriches the body of Buddhist studies by highlighting symbolic practices often overlooked by academics.